ICT use for learning and students' outcomes: Do the country's development level matter? - Luis Vargas-Montoya; Gregorio Gimenez; Marcos Fernández-Gutiérrez (International Telecommunications Society (ITS), 2023)
The use of Information and Communications Technologies (ICT) in educational systems has become a policy priority over the last decades. However, empirical evidence is inconclusive on whether there is a positive relationship between ICT use and students' outcomes. The literature has largely ignored the role that the country context, and in particular the country's development level, may play in shaping this relationship. This paper empirically addresses whether the relationship between ICT use for learning at school and students' outcomes differs from developed to developing countries. We employ data for 236,540 students attending 10,193 schools in 44 countries, obtained from the OECD Programme for International Student Assessment (PISA 2018). We use two alternative measures to classify the countries by their development level: The Gross National Income (GNI) per capita and the Human Development Index (HDI). The estimations, based on a Hierarchical Linear Model, show a negative relationship between ICT use for learning at school and students' outcomes. This negative relationship is more negative for students from developing countries than for those from developed countries. These findings imply that policymakers should be cautious about replicating interventions and technological applications from developed to developing countries (and vice versa).
Keywords: 330; ICT use; education; development; income; PISA